Venezuela and its turtles - Viloria, Ángel L. (Anartia, 2021)
I should say that this, so-called second reissue of The turtles of Venezuela (Pritchard & Trebbau 1984), is actually a true third edition of one of the most outstanding monographs of the chelonians of any region of the American continent. It is essential for institutional, private amateur and professional libraries devoted to the vertebrate fauna of Venezuela and South America. It does not only contain the most relevant, complete and updated information on the chelonian reptile taxa so far recorded in the Venezuelan territory (including its adjacent sea portion of the Caribbean and all rivers, lakes and ponds), but also makes a commendable contribution to the art of book printing in relation to the second edition previously published in Spanish in Caracas (Trebbau & Pritchard 2016).